The Relationship between Tourism Development and Economic Growth in Transition Economies: A Comparative Causality Analysis - Cutcu, Ibrahim; Karis, Cigdem; Sharif, Arshian; Cil, Dilek; Tiwari, Sunil; Çütcü, İbrahim (Springer, 2025)
The purpose of this study is to examine the relationship between tourism development and economic growth in transition economies. For this objective, the symmetric and asymmetric panel causality approach is employed to examine the relationship between economic growth and tourism development in eight EU member transition economies and six non-EU transition economies from 1995 to 2017. The symmetrical causality test results show no evidence of a causal relationship between tourism development and economic growth for both EU and non-EU country groups. The asymmetric causality test did not reveal any evidence of a causal relationship in non-EU transition economies. On the other hand, EU-member transition economies have identified a bidirectional causal relationship between negative components of tourism development and economic growth, and a unidirectional causal relationship between positive components of tourism development. Asymmetric causality test indicates a hidden cause-and-effect relationship for the EU member country group but not for the non-EU country group. Determination of the hidden causality relationship and measurement of positive and negative shocks between tourism development and economic growth significantly contributes in the existing literature. We also expect that the determination of this causality relationship enriches and expands tourism policies in the face of the reactions of positive and negative shocks, and it may guide the development of effective tourism policies that serve as a complement to economic growth and tourism development.
Keywords: Economic growth; Tourism development; Transition economies